Impact of root exudates of different cultivars and plant development stages of rice (Oryza sativa L.) on methane production in a paddy soil - Aulakh, Milkha S.; Wassmann, Reiner; Bueno, C.; Rennenberg, Heinz (Plant and soil, 2001)
The impact of root exudates, collected from five rice cultivars, on methane (CH₄) production was studied in a paddy soil under anaerobic conditions. Root exudates of the cultivars Dular, IR72 and IR65598 collected at four growth stages and of B40 and IR65600 collected at two growth stages showed that (a) CH₄ production was commenced rapidly within 2 h upon exúdate addition and reached a maximum within a day of addition, and (b) 7-d incubation periods were sufficient to study exudate-induced CH₄ production potentials. Among different cultivars, high C releases from roots, increased the methanogenic source strength of the soil, which finally controlled CH₄ production. The relationship of the amount of CH₄ produced was stronger for the amount of total organic C (r = 0.920) than for the amount of organic acids (r = 0.868) added through exudates. Apparently, CH₄ production and CH₄ emission are more closely related to the release pattern of root exudate-C than to its individual components. The proportion of exudate-C converted to CH₄ ranged between 61 and 83% and remained unaffected by cultivars and growth stages suggesting that the majority of exudate-C served as a methanogenic substrate in the anoxic rice soils. These observations indicate that the use of high-yielding cultivars with lowest excretion (for example IR65598, IR65600) would result in lowest exudate-induced CH₄ production. Therefore, cultivar choice could greatly influence regional and global CH₄ emissions and screening/selection of exiting rice cultivars, and/or breeding new cultivars with low exudation rates could offer an important methane mitigation option as long as yields are not compromised.